Effect of erythropoietin on primed leucocyte expression profile. Issue 6 (June 2014) - Pesce, Mirko; Felaco, Paolo; Franceschelli, Sara; Speranza, Lorenza; Grilli, Alfredo; Anna De Lutiis, Maria; Ferrone, Alessio; Sirolli, Vittorio; Bonomini, Mario; Felaco, Mario; Patruno, Antonia
Abstract : Resistance to erythropoietin (EPO) affects a significant number of anaemic patients with end-stage renal disease. Previous reports suggest that inflammation is one of the major independent predictors of EPO resistance, and the effects of EPO treatment on inflammatory mediators are not well established. The aim of this study was to investigate EPO-induced modification to gene expression in primary cultured leucocytes. Microarray experiments were performed on primed ex vivo peripheral blood mononuclear cells (PBMCs) and treated with human EPO-α. Data suggested that EPO-α modulated genes involved in cell movement and interaction in primed PBMCs. Of note, EPO-α exerts anti-inflammatory effects inhibiting the expression of pro-inflammatory cytokine IL-8 and its receptor CXCR2; by contrast, EPO-α increases expression of genes relating to promotion of inflammation encoding for IL-1β and CCL8, and induces de novo synthesis of IL-1α, CXCL1 and CXCL5 in primed cells. The reduction in MAPK p38-α activity is involved in modulating both IL-1β and IL-8 expression. Unlike the induction of MAPK, Erk1/2 activity leads to upregulation of IL-1β, but does not affect IL-8 expression and release. Furthermore, EPO-α treatment of primed cells induces the activation of caspase-1 upstream higher secretion of IL-1β, and this process is not dependent on caspase-8 activation. In conclusion, our findings highlight new potential molecules involved in EPO resistance and confirm the anti-inflammatory role for EPO, but also suggest a plausible in vivo scenario in which the positive correlation found between EPO resistance and elevated levels of some pro-inflammatory mediators is due to treatment with EPO itself.